In Vivo Pravastatin Treatment Reverses Hypercholesterolemia Induced Mitochondria-Associated Membranes Contact Sites, Foam Cell Formation, and Phagocytosis in Macrophages - Assis, Leandro Henrique de Paula; Dorighello, Gabriel de Gabriel; Rentz, Thiago; Souza, Jane Cristina de; Vercesi, Aníbal Eugênio; Oliveira, Helena Coutinho Franco de (Frontiers in Molecular Biosciences, 2022)
Statins are successful drugs used to treat hypercholesterolemia, a primary cause of atherosclerosis. In this work, we investigated how hypercholesterolemia and pravastatin treatment impact macrophage and mitochondria functions, the key cell involved in atherogenesis. By comparing bone marrow-derived macrophages (BMDM) of wild type (WT) and LDL receptor knockout (LDLr-/-) mice, we observed hypercholesterolemia increased the number of contact sites at mitochondria-associated endoplasmic reticulum (ER) membranes (MAM), enhanced mitochondrial hydrogen peroxide release, altered gene expression of inflammatory markers, increased oxidized LDL (ox-LDL) uptake and phagocytic activity. Three months of in vivo pravastatin treatment of LDLr-/- mice reversed the number of contact sites at MAM, ox LDL uptake and phagocytosis in LDLr-/- BMDM. Additionally, pravastatin increased BMDM mitochondrial network branching. In peritoneal macrophages (PM), hypercholesterolemia did not change MAM stability, but stimulated hydrogen peroxide production and modulated gene expression of pro- and anti-inflammatory markers. It also increased mitochondrial branching degree and had no effects on ox-LDL uptake and phagocytosis in PM. Pravastatin treatment increased superoxide anion production and changed inflammation related gene expression in LDLr-/- PM. In addition, pravastatin increased markedly the expression of the mitochondrial dynamics related genes Mfn2 and Fis1 in both macrophages. In summary, our results show that hypercholesterolemia and pravastatin treatment affect macrophage mitochondria network structure as well as their interaction with endoplasmic reticulum (ER). These effects impact on macrophage conversion rates to foam cell and macrophage phagocytic capacity. These findings associate MAM stability changes with known mechanisms involved in atherosclerosis progression and resolution.